Treatment of head lice with dimeticone 4% lotion: comparison of two formulations in a randomised controlled trial in rural Turkey - Sahin M Turhan; Ermiş Özge; Muslu Hasan; Tabak Tuba; Girginkardeşler Nogay; Limoncu M Emin; Burgess Ian F; Balcıoğlu I Cüneyt; Kurt Özgür; Bilac Cemal; Kavur Hakan; Özbel Yusuf (BMC, 2009)
Abstract Background Dimeticone 4% lotion was shown to be an effective treatment for head louse infestation in two randomised controlled trials in England. It is not affected by insecticide resistance but efficacy obtained (70-75%) was lower than expected. This study was designed to evaluate efficacy of dimeticone 4% lotion in a geographically, socially, and culturally different setting, in rural Turkey and, in order to achieve blinding, it was compared with a potential alternative formulation. Methods Children from two village schools were screened for head lice by detection combing. All infested students and family members could participate, giving access to treatment for the whole community. Two investigator applied treatments were given 7 days apart. Outcome was assessed by detection combing three times between treatments and twice the week following second treatment. Results In the intention to treat group 35/36 treated using dimeticone 4% had no lice after the second treatment but there were two protocol violators giving 91.7% treatment success. The alternative product gave 30/36 (83.3%) treatment success, a difference of 8.4% (95% CI -9.8% to 26.2%). The cure rates per-protocol were 33/34 (97.1%) and 30/35 (85.7%) respectively. We were unable to find any newly emerged louse nymphs on 77.8% of dimeticone 4% treated participants or on 66.7% of those treated with the alternative formulation. No adverse events were identified. Conclusion Our results confirm the efficacy of dimeticone 4% lotion against lice and eggs and we found no detectable difference between this product and dimeticone 4% lotion with nerolidol 2% added. We believe that the high cure rate was related to the lower intensity of infestation in Turkey, together with the level of community engagement, compared with previous studies in the UK. Trial Registration Current Controlled Trials ISRCTN10431107